1996
DOI: 10.1172/jci118382
|View full text |Cite
|
Sign up to set email alerts
|

Sex steroids, bone mass, and bone loss. A prospective study of pre-, peri-, and postmenopausal women.

Abstract: Although bone loss around the time of menopause is driven by estrogen deficiency, the roles of estrogens and androgens in the preservation of skeletal mass at other stages of life are less well understood. To address this issue we studied 231 women between the ages of 32 and 77 with multiple measurements of sex steroids and bone mass over a period of 2-8 yr. In all women bone mass was negatively associated with concentrations of sex-hormone binding globulin, and positively associated with weight. Bone loss occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
147
2
8

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(166 citation statements)
references
References 18 publications
8
147
2
8
Order By: Relevance
“…It is well known that the rate of bone loss varies considerably between early postmenopausal and older women and different mechanisms may be involved in each of these periods. (13) The ORIGINAL ARTICLE…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the rate of bone loss varies considerably between early postmenopausal and older women and different mechanisms may be involved in each of these periods. (13) The ORIGINAL ARTICLE…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although women and men both lose bone mineral during aging because of endocrine [6][7][8], paracrine [9,10], and cellular factors [11,12], the effect is more profound in women, beginning even before menopause [13,14], but notably accelerating afterward with rapid decline in estrogen [15,16]. Bone strength, however, is determined not only by the amount of bone mineral, but also by its spatial distribution with respect to the loading forces that may be encountered [17].…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have reported lower sex steroids and higher sex hormone-binding globulin (SHBG) associated with bone loss (5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and increased fracture risk but this is not consistently reported (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), perhaps because many factors influence fracture risk, particularly falls (26,27). However, few prospective data are available examining the contribution of sex steroids and SHBG on fracture risk (15,18,20,22,24).…”
Section: Introductionmentioning
confidence: 99%